The Creative Thinking Skills based on the Learning Autonomy Assisted by Contextual Module and Mentoring (Universitas Negeri Semarang, 2021)
This research aims to describe the effectiveness of independent learning without face-to-face activities assisted by contextual module and mentoring toward the creative thinking skills. This research is a combined research with sequential explanatory design. The population of this research consisted of seventh graders of Public JHS 31 Semarang in academic year 2018/2019. The sample consisted of the VII H class learners. They were taken based on three self-confidence categories: high, moderate, and low. Techniques of collecting data were test, interview, and documentation. The findings showed that the autonomous learning assisted by the contextual module and the mentoring was effective. From the six learners with high learning autonomy, they showed a moderate creative thinking skill. From 21 learners with moderate learning autonomy, 11 learners were found to have a moderate creative thinking skill while 10 learners had a low creative thinking skill. From 5 learners with low learning autonomy, 4 learners had a low creative thinking skill while one learner had a moderate creative thinking skill.